Whiteness and non-racialism: White students’ discourses of transformation at UCT - Urson, Ruth; Kessi, Shose (PINS-Psychology in Society, 2018)
Recent years have seen black university students in South Africa rallying against institutional racism and mobilising for systemic change in higher education, in response to the slow progress of transformation. Against this backdrop, little is known about white students’ perceptions. In this paper, we examine white students’ understandings of non-racialism and their roles in racial transformation. A Whiteness Studies framework was used to investigate how white students talk about transformation and race at the University of Cape Town (UCT), and what role these discourses play in transformation. Four focus groups were conducted in 2015 with 27 white UCT students from different programmes of study, and a discourse analysis incorporating Foucauldian principles was used to analyse these discussions. Three discursive sets of Old Order Whiteness, Defensive Rainbowism and a developing set of counter-discourses were identified, according to the influence that broader discourses used in constructing race and transformation had on white students’ positioning. The use, interrogation and challenging of these discursive sets by participants demonstrates a discursive negotiation and fracturing within this sample group, with potential implications for non-racialism and the transformation process.